Histological features and severity of oxaliplatin‐induced liver injury and clinical associations. Issue 10 (October 2014) - Nalbantoglu, ILKe; Tan, Benjamin R; Linehan, David C; Gao, Feng; Brunt, Elizabeth M
<x xml:space="preserve">Abstract</x> Objective Oxaliplatin, a component of chemotherapy for colorectal carcinoma liver metastases, can result in hepatic sinusoidal injury; rarely, the injury is fatal. The manifestations of injury are variable. There are no known predictors of susceptibility and outcome. A semi‐quantitative system for assessing histological features in non‐tumor liver was designed to compare with clinical short‐term and long‐term outcomes. Methods A review of 47 patients with metastatic colorectal carcinoma who received liver resection utilizing a system for an aggregate liver injury score (0–4) included hepatocellular and sinusoidal features. Immunohistochemistry (IHC) for aberrant capillarization was included. The proliferation of hepatocytes and sinusoidal lining cells was evaluated with Ki‐67 stain. Results In total, 32 (68.1%) cases showed light microscopic lesions of oxaliplatin‐induced liver injury, in which 26 were moderate to severe. Elevated preoperative aspartate aminotransferase (AST) and alkaline phosphatase levels were noted with higher injury scores (P = 0.01). Patients with higher injury scores had no significant increase in short‐term postoperative complications, with one notable exception, who died of liver failure 10 months postoperatively. Increased CD34 expression was associated with higher injury scores (P = 0.00004), and abnormal AST levels (P = 0.04). Preoperative use of bevacizumab was not associated with lower injury scores. Steatosis was correlated with body mass index (P = 0.052) but not with exposure to oxaliplatin, bevacizumab or irinotecan. Conclusions The proposed liver injury scoring system encompasses the spectrum of sinusoidal and hepatocellular lesions in oxaliplatin‐induced liver injury and is correlated with serum liver enzyme levels in this group. Most patients recovered without complications during the 93‐month follow‐up, indicating that these lesions are reversible.